The Cultural Proficiency Manifesto : Finding Clarity Amidst the Noise. - Lindsey, Randall B. (SAGE Publications, 2017)
A call-to-arms for educators in tumultuous times In times of social disruption and uncertainty, Cultural Proficiency can provide educators with essential tools for promoting greater equity and inclusion. This book places today's political rancor and divisiveness in the context of greater historical change and provides a roadmap to interrupting the cycle of hostility towards marginalized groups. Readers will find: Esteemed author Randall Lindsey's latest thinking on Cultural Proficiency A deliberately brief format that unpacks the Cultural Proficiency Framework and offers practical guidance